Evaluación de la actividad antiinflamatoria de una crema a partir del extracto purificado de Baccharis Tricuneata (L.f.) Pers. “taya” - Díaz y Cols., Marlon (2019)
The genus Baccharis is one of the most important sources of products in the natural medicine, are distributed in the North and South America and in our country in the high Andean areas, arousing the interest of their usage etnofarmacologico. The species Baccharis tricuneata (L. f.) Pers. "Taya", is used in traditional medicine in the antiinflammatory therapy in the form of poultices. The ethyl acetate extract was obtained from the ethanolic extract by successive fragmentations using solventsincreasing polarity. It carried out the identification of flavonoids in the extracts showing greater presence in the ethyl acetate extract. It was formulated and assessed the antiinflammatory activity of an ointment prepared from the extract of ethyl acetate to various concentrations. Pharmacological evaluation was performed by themethod of ear edema induced by Croton Oil. The cream to the 30% showed antiinflammatory activity of 71.43 %. It is attributed to the flavonoids the antiinflammatory activity found that there are already reports of his great power to stabilize membranes and oxidizing radicals.